PENATALAKSANAAN FISIOTERAPI PADA KONDISI PIRIFORMIS SINDROME DEKSTRA DENGAN MODALITAS MICRO WAVE DIATHERMI, ULTRA SOUND DAN TERAPI LATIHAN - Faisol Ridho; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
Piriformis syndrome is a neuromuscular disorder that occurs due to sciatica nerve (nerve ischiadicus) compressed or irritated by the piriformis muscle causing pain, tingling, and numbness in the buttocks area until the sciatica nerve travels. Approximately 15% of the population of cases of sciatica (ischialgia) is piriformis syndrome. To determine the implementation of physiotherapy in reducing pain, muscle spasms, increase muscle strength, and improve the ability of functional activity in conditions with piriformis syndrome modalities micro wave diathermy, ultrasound and exercise therapy. After treatment for 6 times in getting the results of the reduction of pain, decrease muscle spasms, increased muscle strength and functional capacity building activity. Micro wave diatermy can reduce pain and muscle spasm in conditions of piriformis syndrome, and exercise therapy can improve muscle strength and functional activities can improve the condition of the piriformis syndrome.